Associação entre características agronômicas da batata nos plantios de primavera e outono no Rio Grande do Sul - Andreu, Mario Alejandro (2005)
The objective of this work was to identify potato characteristics that have higher adaptation stability for important agronomic characteristics for the contrasting autumn and spring climatic conditions of Rio Grande do Sul, Brazil. The tuber characteristics evaluated were maturity, average number of tuber plant yield, texture, tuber shape, depth of eyes and general appearance. Reduced tuber quality and yield were observed in the autumn crop compared to the spring, due to variations in temperature, radiation and photoperiod. Coefficient of variation were higher in the autumn, in particular for plant yield, average number of tubers, texture and general appearance. Correlation coefficients were moderately high and significant (r < 0,80) for texture, tuber shape and depth of eyes, and low (r < 0,40) for maturity, number of tubers, plant yield and general appearance. The results of this study showed that the characteristics and population studied, the plant productivity and number of tubers are not constant parameters comparing crops in contrasting climates. Characteristics such as texture, tuber shape and depth of eyes can be selected with high intensities, based on their high stability. Selection based on tuber general appearance may be more intense in the spring, when the quality and productivity parameters are maximized.